DETERMINATION OF ASCORBIC ACID CONCENTRATION IN MYRTACEAE USING THE IODOMETRIC TITRATION METHOD - Nur Syafitri; Muhammad Abdurrahman Munir; Veriani Aprilia; Emelda Emelda (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2023)
Vitamins are essential compounds in food even though the content contained in these foods is small, and this is because vitamins have a vital role in the human body. Vitamin C or ascorbic acid is a secondary antioxidant compound that captures free radical compounds. Vitamin C content is easily found in vegetables and fruits. One of the fruits that contain vitamin C is guava. This study aims to determine and analyze vitamin C concentrations in several guava fruit types with the iodometric titration method. This type of research is a quantitative-qualitative experimental laboratory. The samples used in this study were guava in Myrtaceae family consisting of red guava (Psidium guajava L.), crystal guava (Psidium guajava L.), and red water guava (Syzygium aqueum). The study began with making 0.05 N iodine, iodine formation, then the 3% amylum indicators. The average sample content of red guava, crystal guava, and red water guava was 2.42 mg/100 grams. To conclude, the ascorbic acid concentration of red guava water is higher at 157 mg/100 g compared to the other two guavas, which are 80 mg/100 g and 87 mg/100 g.